Cloud Foundry for developers : deploy, manage, and orchestrate cloud-native applications with ease - Farmer, Rick; Jain, Rahul; Wu, David (Packt Publishing, 2017)
Deploy and scale applications on Cloud Foundry About This Book Gain hands-on experience using Cloud Foundry Implement deployment, management and scaling of applications on Cloud Foundry Learn best practices and troubleshooting tips for running applications on Cloud Foundry Who This Book Is For This book is aimed at developers, engineers and architects who want to learn key aspects of developing and running applications on the Cloud Foundry Platform. Prior knowledge Cloud Foundry is not necessary. What You Will Learn Understand Cloud Foundry (CF) tools and concepts. Understand the breadth of possibilities unleashed through a lightweight agile approach to building and deploying applications. Design and deploy cloud native applications that run well on Cloud Foundry. Learn Microservice design concepts and worker applications. Customize service brokers to publish your services in the Cloud Foundry marketplace. Using, managing and creating buildpacks for the Cloud Foundry Platform. Troubleshoot applications on Cloud Foundry Perform zero-downtime deployments using blue/green routes, A/B testing, and painless rollbacks to earlier versions of the application. In Detail Cloud Foundry is the open source platform to deploy, run, and scale applications. Cloud Foundry is growing rapidly and a leading product that provides PaaS (Platform as a Service) capabilities to enterprise, government, and organizations around the globe. Giants like Dell Technologies, GE, IBM, HP and the US government are using Cloud Foundry innovate faster in a rapidly changing world. Cloud Foundry is a developer's dream. Enabling them to create modern applications that can leverage the latest thinking, techniques and capabilities of the cloud, including: DevOps Application Virtualization Infrastructure agnosticism Orchestrated containers Automation Zero downtime upgrades A/B deployment Quickly scaling applications out or in This book takes readers on a journey where they will first learn the Cloud Foundry basics, including how to deploy and scale a simple application in seconds. Readers will build their knowledge of how to create highly scalable and resilient cloud-native applications and microservices running on Cloud Foundry. Readers will learn how to integrate their application with services provided by Cloud Foundry and with those external to Cloud Foundry. Readers will learn how to structure their Cloud Foundry environment with orgs and spaces. After that, we'll discuss aspects ...